G6pd-Deficient Mice Are Protected From Experimental Cerebral Malaria and Liver Injury by Suppressing Proinflammatory Response in the Early Stage of Plasmodium berghei Infection - Yi, Haoan; Jiang, Weiyang; Yang, Fang; Li, Fan; Li, Yirong; Zhu, Wenjing; Li, Qing; Fakhar, Syed Hassam; Cao, Yaming; Luo, Lan; Zhang, Wen; He, Yongshu (Frontiers in Immunology, 2021)
Epidemiological studies provide compelling evidence that glucose-6-phosphate dehydrogenase (G6PD) deficiency individuals are relatively protected against Plasmodium parasite infection. However, the animal model studies on this subject are lacking. Plus, the underlying mechanism in vivo is poorly known. In this study, we used a G6pd-deficient mice infected with the rodent parasite Plasmodium berghei (P.berghei) to set up a malaria model in mice. We analyzed the pathological progression of experimental cerebral malaria (ECM) and acute liver injury in mice with different G6pd activity infected with P.berghei. We performed dual RNA-seq for host-parasite transcriptomics and validated the changes of proinflammatory response in the murine model. G6pd-deficient mice exhibited a survival advantage, less severe ECM and mild liver injury compared to the wild type mice. Analysis based on dual RNA-seq suggests that G6pd-deficient mice are protected from ECM and acute liver injury were related to proinflammatory responses. Th1 differentiation and dendritic cell maturation in the liver and spleen were inhibited in G6pd-deficient mice. The levels of proinflammatory cytokines were reduced, chemokines and vascular adhesion molecules in the brain were significantly down-regulated, these led to decreased cerebral microvascular obstruction in G6pd-deficient mice. We generated the result that G6pd-deficiency mediated protection against ECM and acute liver injury were driven by the regulatory proinflammatory responses. Furthermore, bioinformatics analyses showed that P.berghei might occur ribosome loss in G6pd-deficient mice. Our findings provide a novel perspective of the underlying mechanism of G6PD deficiency mediated protection against malaria in vivo.